Preoperative predictors of portal vein thrombosis after splenectomy with periesophagogastric devascularization - Zhang, Yu (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate the predictive value of preoperative predictors for portal vein thrombosis (PVT) after splenectomy with periesophagogastric devascularization. METHODS: In this prospective study, 69 continuous patients with portal hypertension caused by hepatitis B cirrhosis underwent splenectomy with periesophagogastric devascularization in West China Hospital of Sichuan University from January 2007 to August 2010. The portal vein flow velocity and the diameter of portal vein were measured by Doppler sonography. The hepatic congestion index and the ratio of velocity and diameter were calculated before operation. The prothrombin time (PT) and platelet (PLT) levels were measured before and after operation. The patients’ spleens were weighed postoperatively. RESULTS: The diameter of portal vein was negatively correlated with the portal vein flow velocity (P < 0.05). Thirty-three cases (47.83%) suffered from postoperative PVT. There was no statistically significant difference in the Child-Pugh score, the spleen weights, the PT, or PLT levels between patients with PVT and without PVT. Receiver operating characteristic curves showed four variables (portal vein flow velocity, the ratio of velocity and diameter, hepatic congestion index and diameter of portal vein) could be used as preoperative predictors of postoperative portal vein thrombosis. The respective values of the area under the curve were 0.865, 0.893, 0.884 and 0.742, and the respective cut-off values (24.45 cm/s, 19.4333/s, 0.1138 cm/s(-1) and 13.5 mm) were of diagnostically efficient, generating sensitivity values of 87.9%, 93.9%, 87.9% and 81.8%, respectively, specificities of 75%, 77.8%, 86.1% and 63.9%, respectively. CONCLUSION: The ratio of velocity and diameter was the most accurate preoperative predictor of portal vein thrombosis after splenectomy with periesophagogastric devascularization in hepatitis B cirrhosis-related portal hypertension.